Traders at Work How the Worlds Most Successful Traders Make Their Living in the Markets - Bourquin, Tim. (Apress : Imprint: Apress, 2013)
Shortly after most novice traders discover how trading works and begin to realize that they have the potential to make unlimited amounts of money in the financial markets, they start dreaming the near-impossible dream. They fantasize about buying that condo in Boca Raton for their parents or surprising their son with a brand-new car on his 16th birthday. They even begin to imagine themselves opening their own trading firm or milling about the pit of the Chicago Mercantile Exchange, lobbying against other professional traders for the perfect entry into a once-in-a-lifetime trade. But then ... they watch the markets lurch in wildly unpredictable ways, lose their shirts in a few live trades, and then freeze in their tracks, wondering if they will ever be able to consistently trade in a manner that can even loosely be defined as profitable. To be sure, becoming a full-time, professional trader, working at a proprietary trading firm, or managing the trading activity of a hedge fundmay sound like the perfect career, but its all too easy for beginner traders to overestimate their trading abilities, underestimate the movements of the markets, and find themselves in a financial hole of epic proportions after a few bad trades. So what does it really take to make a living in the markets? Tim Bourquin, co-founder of Traders Expo and the Forex Trading Expo and founder of TraderInterviews.com, and freelance writer and editor Nick Mango set out to answer that exact question in Traders at Work, a unique collection of over 20 interviews with some of the worlds most successful professional traders, from at-home hobbyists who have opened their own firms to those working at hedge funds, on proprietary trading desks, and in exchange pits. What mistakes did Anne-Marie Baiynd make early in her career? What does Michael Toma wish he had known about trading? What trading strategies work best for Linda Raschke? How does John Carter remain cool, calm, and collected when the markets are sending mixed signals? And how did Todd Gordon make the transition from part-time to full-time trader? Bourquin and Mango ask all of these questions and more in Traders at Work and in doing so reveal insider insights on what it takes to be a successful trader from those who are living that dream. Fascinating, compelling, and filled with never-before-told stories from the front lines of the trading arena, Traders at Work is required reading for anyone who has ever asked themselves if they have what it takes to trade for a living.